Leveraging the Metaverse for Sustainable Practices in Retail Business: Opportunities and Challenges. - Mujibur Rahman; Mohammad Akhtar (Journal of Technology Management & Innovation)
The retail industry driven by the emergence of advance technologies as well as changing consumer behaviour has evolved significantly. The metaverse offers vast potential for sustainable retail and has emerged as a transformative force in the world of digital experiences. By embracing the metaverse technologies, sustainable retail businesses can pioneer innovative solutions that can promote environmental and social sustainability while enhancing operational efficiencies and consumer’s immersive engagements and experiences. This paper delves into the emerging applications of the metaverse in shaping sustainable retail practices and additional revenue stream. It also examines the potential risks and challenges associated with integrating metaverse technologies into sustainable retail strategies.